Cardiopulmonary Exercise Testing in Lung Transplantation: A Review - Katherine A. Dudley; Souheil El-Chemaly (Pulmonary Medicine)
There has been an increase in lung transplantation in the USA. Lung allocation is guided by the lung allocation score (LAS), which takes into account one measure of exercise capacity, the 6-minute walk test (6MWT). There is a paucity of data regarding the role and value of cardiopulmonary stress test (CPET) in the evaluation of lung transplant recipients while on the transplant waiting list and after lung transplantation. While clearly there is a need for further prospective investigation, the available literature strongly suggests a potential role for CPET in the setting of lung transplant.